The Utility of Bone Burring for the Clearance of Locally Advanced Scalp Malignancies: A Scoping Review - Ojochonu D. Anthony, BBiomedSc; David J. Hunter-Smith, MBBS, FRACS, FACS; Warren M. Rozen, MD, PhD, FRACS (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. The scalp harbors a range of neoplasms occurring at inordinate rates and associated with poorer outcomes. Its unique anatomy poses surgical challenges, including clear deep margins when resecting these lesions. For malignancies extending to the pericranium, removal of outer cortical cranial bone is ideal and routinely achieved with a burr. This review aims to investigate the literature to ascertain the utility and safety of this technique while highlighting evidence gaps. Methods:. A literature search was conducted systematically using MEDLINE, Embase, and PubMed. Articles were reviewed for inclusion, and eligible studies were analyzed for study design, patient and intervention details, and outcome measures. A formal statistical analysis was not conducted. Results:. The original search yielded 1506 unique results, and eight studies met the inclusion criteria: four case series, two retrospective analysis of records, two case reports. A number of tumor types were identified, but the burring method used was consistent in all studies. Despite reassuring primary outcome measure results, specifically in terms of local control rates, the overall evidence quality is limited by the nature of the included studies. Few adverse events were reported. Conclusions:. Evidence for the oncological efficacy of scalp bone burring remains limited. Although the technique seems relatively safe, further investigation is required into its utility and drawbacks. Future studies should aim to report more technical details and more information about outcomes. It may also be worth comparing burring to alternatives such as outer cortical splitting, curettage, and high-dose curative radiotherapy.